2019
DOI: 10.1167/iovs.18-24921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Choroidal Vessel Density on the Ellipsoid Zone and Visual Function in Retinitis Pigmentosa Using Optical Coherence Tomography Angiography

Abstract: PURPOSE. We evaluate the effect of choroidal vessel density on the residual length of the ellipsoid zone (EZ) and visual function in patients with retinitis pigmentosa (RP) using optical coherence tomography angiography (OCTA). METHODS. Fifty-three patients with RP (n ¼ 101 eyes) and 53 normal participants (n ¼ 76 eyes) were enrolled in this study. Patients with RP were assigned to three groups according to their best-corrected visual acuity (BCVA). All patients underwent ophthalmologic examinations, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…This result inspired the hypothesis that visual acuity can be an indicator of retinal vessel circulation change. Similar results were derived from Liu's study (31) that vessel density was a prominent factor affecting visual acuity. The underlying mechanism may be that nerve fiber and ganglion cell layer receive blood from the superficial retinal vascular plexus and the degree of perfusion may impact visual performance (32).…”
Section: Discussionsupporting
confidence: 86%
“…This result inspired the hypothesis that visual acuity can be an indicator of retinal vessel circulation change. Similar results were derived from Liu's study (31) that vessel density was a prominent factor affecting visual acuity. The underlying mechanism may be that nerve fiber and ganglion cell layer receive blood from the superficial retinal vascular plexus and the degree of perfusion may impact visual performance (32).…”
Section: Discussionsupporting
confidence: 86%
“…Several recent studies conducted with OCTA have reported a reduction of retinal vessel density and retinal perfusion density, impaired choroidal blood flow, or significantly altered sizes of the foveal avascular zones in eyes of patients suffering from RP [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Given the known microvascular alterations in RP, it might be beneficial to use OCTA in the context of TES treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Successive improvement in technology and instrumentation provided the possibility of using enhanced depth imaging (EDI) using spectral domain optical coherence tomography to study the choroid. This method has opened a new window in understanding choroidal physiopathology in normality and disease [23][24][25][26][27][28][29][30]. OCT methods have rapidly improved, and angiography has been included, thus giving rise to OCT-A, which has revolutionized the evaluation of retinal and choroidal perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…The choroid is the principal source of nutrients and oxygen to the retinal pigment epithelium-photoreceptor layer, as the outer retinal layers do not have a vascular network [30,31]. The photoreceptors have a high metabolic activity, and more than 90% of the oxygen received by the retina is used by the photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation